Heirs, corporate aristocrats and 'Meritocrats': the social space of top CEOs and Chairmen in India. (19th April 2018) - Naudet, Jules; Allorant, Adrien; Ferry, Mathieu
Abstract: This article proposes an analysis of the social space inhabited by the CEOs and Chairmen of the top 100 Indian companies in 2012, using a Multiple Correspondence Analysis (MCA). The analysis aims to understand the internal divisions to be found in the field of economic power, by looking at the divisions along the lines of educational capital, inherited capital (family capital), caste and social capital (drawing on a network analysis of interlocking directorates). Our results point to a very peculiar structuration of the economic field; we find that credentialism has a very weak influence, there is a clear and massive cleavage between owners and managers of capital, social capital carries decisive weight and the actors closest to the state apparatus occupy a marginal role. We argue that it is possible to identify three poles among business leaders: the multipositional family business owners, the unipositional family business owners and the managerial galaxy.